The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.20944/preprints201804.0354.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of TRPV1 Function in Human CD4+ T Cells by Nanodiamond and Nanoplatinum Liquid, DPV576

Abstract: Transient receptor potential vanilloid (TRPV) channels act as sensors of pain, temperature, and other external stimuli. We have recently shown that DPV576, an aqueous mixture of nanodiamond (ND) and nanoplatinum (NP), can modulate the activity of TRPV on human primary keratinocytes, suggesting their potential as a possible pain modulator [1]. CD4+ T lymphocytes also express TRPV channels, and we sought with special interest to examine the effect of DPV576 in modulating the functions of TRPV channel expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated the capacity of NDs to elicit highly specific immune responses by affixing different antibodies and small molecules to their surface (Suarez-Kelly et al, 2021;Paladhi et al, 2022). A few of the many examples include enhanced proliferation of CD4 + and CD8 + T-cells (Ghoneum et al, 2014), B-lymphocytes (Huang et al, 2017;Suarez-Kelly et al, 2017), macrophages (Pentecost et al, 2019), and neutrophils (Chang et al, 2003).…”
Section: Nanodiamonds and Immunogenicitymentioning
confidence: 99%
“…Studies have demonstrated the capacity of NDs to elicit highly specific immune responses by affixing different antibodies and small molecules to their surface (Suarez-Kelly et al, 2021;Paladhi et al, 2022). A few of the many examples include enhanced proliferation of CD4 + and CD8 + T-cells (Ghoneum et al, 2014), B-lymphocytes (Huang et al, 2017;Suarez-Kelly et al, 2017), macrophages (Pentecost et al, 2019), and neutrophils (Chang et al, 2003).…”
Section: Nanodiamonds and Immunogenicitymentioning
confidence: 99%
“…Moreover, Ti02 nanoparticles were able to induce DC maturation and produce inflammatory cytokines . In addition, nanodiamond and nanoplatinum liquid can induce DC maturation . Thus, many NPs can influence DC maturation and induction of immune responses but the extent of which, their mechanisms, and whether all NPs can signal through TLR receptors needs further investigation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…From one side, the fabric itself hosts the bacteria acting as a medium between the human organism and the microorganisms; on the other hand, it is regarded as a well assessed tool for drug delivery in contact of skin for external applications [24][25][26]. Therefore wide market sectors push textile industries to concentrate more on antibacterial fabrics manufacturing to improve fabrics quality and product sales.…”
Section: Introductionmentioning
confidence: 99%